Deconvolution-Based System Identification and Finite Element Model Calibration of the UCLA Factor Building - Fei Wang; Jiemei Ma; Xiandong Kang; Qixuan Liu; Hongyu Chen (Buildings, 2024)
Analysis of wave propagation within buildings in response to earthquakes enables the tracking of changes in dynamic characteristics using impulse response functions. The velocity of traveling shear waves and the intrinsic attenuation of buildings can be retrieved, providing valuable input for system identification. The Factor Building at the University of California, Los Angeles campus (henceforth referred to as the UCLA Factor Building), an instrumented 15-story steel moment frame structure, is selected for dynamic response characterization. Shear wave travel time and attenuation are computed from wave propagation using seismic interferometry applied to recorded motions, with deconvolved waves used to compute these parameters. In this study, the natural logarithm of the envelopes of waveforms deconvolved with the basement signal provided the measure of attenuation. Additionally, the waveforms deconvolved with the basement motion, indicating the building’s fundamental mode. The frequency and time decay further constrained the shear velocity and attenuation. Shear velocity was determined using arrival times measured from deconvolved waves, resulting in an average velocity of 147.1 m/s. The observed quality factor was 10.8, with a corresponding damping ratio of 5%. The shear wave velocity and damping ratio estimates derived from deconvolved waves showed consistency with those obtained from basement deconvolved waveforms. This consistency validates wave deconvolution as an effective method for isolating building response from excitation and ground coupling. By incorporating the resonant frequencies and damping ratios derived from previous analyses into a refined element model, this study underscores the potential of wave deconvolution for extracting building dynamic characteristics, thereby enhancing our understanding of their responses to earthquakes.